2023
DOI: 10.36902/sjesr-vol6-iss1-2023(169-175)
|View full text |Cite
|
Sign up to set email alerts
|

Level of Academic Stress and its Influence on the Academic Achievements of Students at Mirpur University of Science and Technology

Abstract: Academic Stress among university students is a major problem that may negatively affect their grades. Students often experience academic pressure because of the difficulties they face at the university level. This quantitative study aims to evaluate the level of academic stress among the students of Mirpur University of Science and Technology (MUST), Mirpur, Azad Jammu & Kashmir, and its effect on their academic achievements. For this purpose, the causal-comparative research design was used, and the “Acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Mental health problems in general, and academic stress in particular, are quite common among college students (Fawzy, 2017;Gurung et al, 2020;Trigueros et al, 2020;Pascoe, 2020;Yang et al, 2021) it has a negative impact on students' academic performance (Tus, 2020;Rehman et al, 2023) and is one of causes of dropout (Eicher et al, 2014;Marôco et al, 2020;Noman et al, 2021). Academic stress is understood as a psychological expression caused by academic and social pressures (Misra & Castillo, 2004;Neseliler, 2017), it is a complex problem that includes many emotional, social, and academic stressors (Misra & McKean, 2000).…”
Section: Academic Stress Of Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health problems in general, and academic stress in particular, are quite common among college students (Fawzy, 2017;Gurung et al, 2020;Trigueros et al, 2020;Pascoe, 2020;Yang et al, 2021) it has a negative impact on students' academic performance (Tus, 2020;Rehman et al, 2023) and is one of causes of dropout (Eicher et al, 2014;Marôco et al, 2020;Noman et al, 2021). Academic stress is understood as a psychological expression caused by academic and social pressures (Misra & Castillo, 2004;Neseliler, 2017), it is a complex problem that includes many emotional, social, and academic stressors (Misra & McKean, 2000).…”
Section: Academic Stress Of Studentsmentioning
confidence: 99%
“…The university learning environment is new, complex and difficult (Arguel et al, 2017;Lodge et al, 2018;Agyekum, 2023;Bernardo et al, 2023), these difficulties can lead to various problems in students, including mental health issues (Yikealo et al, 2018;Mofatteh, 2020;Hernández-Torrano et al, 2020;Campbell et al, 2022). When mental health problems in general and academic stress in particular arise, they can negatively impact students' health, quality of life, and academic performance (Ícaro et al, 2018;Tus, 2020;Barbayannis et al, 2022;Rehman et al, 2023), and is one of the factors leading to intention to leave and drop out of school (Kim, 2021;Abreu Alves et al, 2022;Peng et al, 2023). Many recent reports and studies have found that it is not uncommon for students to choose to drop out of school at some point during their university studies and is common among fifthyear students.…”
Section: Introductionmentioning
confidence: 99%